Leukemic fusion genes MLL/AF4 and AML1/MTG8 support leukemic self-renewal by controlling expression of the telomerase subunit TERT - Gessner, Anja; Thomas, M.; Garrido Castro, P.; Büchler, L.; Scholz, A.; Brümmendorf, T. H.; Martínez Soria, Natalia; Vormoor, J.; Greil, Johann; Heidenreich, O. (Leukemia, 2010)
MLL/AF4 and AML/MTG8 represent two leukemic fusion genes, which are most frequently found in infant acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML), respectively. We examined the influence of MLL/AF4 and AML1/MTG8 fusion genes on the expression of TERT coding for the telomerase protein subunit, and subsequently telomerase activity in t(4;11)-positive ALL and t(8;21)-positive cell lines, respectively. MLL/AF4 suppression diminished telomerase activity and expression of TERT. Blocking pro-apoptotic caspase activation in conjunction with MLL/AF4 knockdown enhanced the inhibition of TERT gene expression, which suggests that MLL/AF4 depletion does not reduce TERT expression levels by inducing apoptosis. Knockdown of HOXA7, a direct transcriptional target of MLL/AF4 fusion gene, caused a reduction of telomerase and TERT to an extent similar to that observed with MLL/AF4 suppression. Chromatin immunoprecipitation of SEM cells, using ectopically expressed FLAG-tagged Hoxa7, indicates HOXA7 binding site in the TERT promoter region. Furthermore, suppression of the AML1/MTG8 fusion gene was associated with severely reduced clonogenicity, induction of replicative senescence, impaired TERT expression and accelerated telomere shortening. We thus present findings that show a mechanistic link between leukemic fusion proteins, essential for development and maintenance of leukemia, and telomerase, a key element of both normal and malignant self-renewal.